Recurrent anal fistulas: When, why, and how to manage? - Emile, Sameh Hany (World J Clin Cases, 2020)
Anal fistula is a commonly encountered anal condition in the surgical practice. Despite being a benign condition, anal fistula remains to represent a surgical challenge, particularly the complex type of fistulas. One of the common complications of anal fistula surgery is the persistence or recurrence of the pathology, both defined as failure of surgery. Recurrent anal fistulas after previous surgery represent an even more challenging problem since they are usually associated with a higher risk of re-recurrence and continence disturbance. The present review aimed to shed light on various aspects of recurrent anal fistulas, including the different definitions of failure after surgery, risk factors of recurrence, problems associated with management of recurrent fistulas, and assessment and treatment of recurrent anal fistulas.